Segmentation Based on Personal and Spiritual Life Balance During Covid-19, and Its Relations with Materialism, Frugality, Well-Being, and Positive Emotions - Cucato, Jussara; Bizarrias, Flávio Santino; Silva, Jussara Goulart; Ferreira, Marlette Cássia de Oliveira (Journal of Sustainable Competitive Intelligence, 2022)
Purpose: TThe objective of this study is to analyze the relationships between material, or frugal, consumption and the congruence between personal and spiritual life, mediated by the search for well-being, generating a segmentation proposal. Methodology/approach: Structural Equation Modeling and regression tests were used for mediation and moderation analysis, complemented by Latent Class Analysis for sample segmentation Originality/Relevance: The study pioneeringly investigates material, frugal, and wellness consumption relationships, as well as the indirect role of positive emotions with the congruence between personal and spiritual life, to propose a segmentation of consumers in a crisis situation. Key findings: The results indicated that well-being and positive emotions allow for moderate mediation, enabling consumers to reconcile both frugal and material goals with a balanced life, individually and spiritually. The proposed segmentation identified three distinct groups based on congruence between practical and spiritual life. Theoretical/methodological contributions: The study advances the understanding of heterogeneous consumer profiles in crisis situations, proposing to practitioners and policymakers to better know the profile of consumers in a health crisis. Methodologically the study combines structural equation modeling, mediation and moderation analysis, and latent class analysis to reach the study’s objective.